1960
DOI: 10.1111/j.1476-5381.1960.tb00275.x
|View full text |Cite
|
Sign up to set email alerts
|

The Anticholinesterase Activity of Some Antiadrenaline Agents

Abstract: The contractions of the isolated guinea-pig vas deferens in response to stimulation of the sympathetic hypogastric nerve were potentiated by low concentrations and inhibited by high concentrations of the antiadrenaline agents tolazoline, yohimbine, ergotamine, phenoxybenzamine and piperoxan. Eserine potentiated the contractions of the vas deferens produced by hypogastric nerve stimulation. The cholinesterase activity of an extract of vas deferens was decreased by the antiadrenaline agents. The potentiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 11 publications
9
72
0
Order By: Relevance
“…A similar phenomenon has also been seen in the vas deferens (Boyd, Chang & Rand, 1960;Bulbring, 1968;Ambache & Zar, 1971;Drew, 1977a). Bulbring (1968) demonstrated that phenoxybenzamine potentiates responses to both direct and indirect (neuronal) stimulation of the vas deferens and Drew (1977a) suggested that its postsynaptic potentiating action is unrelated to an action on a-adrenoceptors.…”
Section: Potentiation Ofthe Twitch By Adrenoceptor Antagonistsmentioning
confidence: 63%
“…A similar phenomenon has also been seen in the vas deferens (Boyd, Chang & Rand, 1960;Bulbring, 1968;Ambache & Zar, 1971;Drew, 1977a). Bulbring (1968) demonstrated that phenoxybenzamine potentiates responses to both direct and indirect (neuronal) stimulation of the vas deferens and Drew (1977a) suggested that its postsynaptic potentiating action is unrelated to an action on a-adrenoceptors.…”
Section: Potentiation Ofthe Twitch By Adrenoceptor Antagonistsmentioning
confidence: 63%
“…The fact that these two drugs, though weaker than LSD, possess the ability to inhibit the motor transmission in the vas deferens (Boyd, Chang & Rand, 1960;Birmingham & Wilson, 1963) has been generally attributed to their well known x-adrenoceptor blocking property. This misconception has been removed in the present experiments by the use of LSD, which exerts an inhibitory action similar to that of ergotamine and dihydroergotamine on the motor transmission in the vas, but does so without producing any block of ox-adrenoceptors in the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In the vas deferens it is well established that the height of the contractile response to nerve stimulation is resistant to reduction by a-adrenoceptor antagonists (Boyd, Chang & Rand, 1960;Ambache & Zar, 1971) at concentrations which increase the nerveinduced output of NA (Stjarne, 1973;Vizi, Somogyi, Hadhazy & Knoll, 1973). In order to explain this it has been suggested that the effector response is adrenergic but resistant to post-junctional blockade (Swedin, 1971;Furness, 1974) or alternatively due to a separate set of 'non-adrenergic' nerves (Ambache © Macmillan Journals Ltd 1979& Zar, 1971.…”
Section: Introductionmentioning
confidence: 99%